Harnessing administrative data in legal epidemiology: new frontiers in the study of family law - Jay, Matthew; Gilbert, Ruth (International Journal of Population Data Science, 2018)
Background In all decisions concerning the upbringing of a child, the child’s best interests are a primary consideration (art 3(1) UN Convention on the Rights of the Child 1989). The extent to which the English family justice system (FJS) promotes children’s well-being, however, is not clear due to a lack of research in this area. In particular, very little is known about educational trajectories and outcomes of looked after children and children in need. Methods This poster will describe administrative data resources generated by the FJS and education sectors and will describe an on-going project examining educational outcomes in vulnerable children. We will use the national children looked after (SSDA903) and child in need returns, linked to the National Pupil Database to examine factors predicting the nature and quality of secondary schools that children in care and in need attend and whether these differ from the general population. Further, we will examine, given the schools that children attend, how secondary school outcomes (absences, exclusions and exam results) vary among different groups of children. Conclusion This project will demonstrate how we can use linked administrative data to evaluate the operation of law and, importantly, substantive outcomes for the children whom it affects. Such studies enable us to monitor changes in policy and practice and thereby evaluate the effectiveness of law.